1977
DOI: 10.1007/bf00566530
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of ethanol absorption and elimination in twins and supplementary repetitive experiments in singleton subjects

Abstract: The influence of genetic and environmental factors on the metabolism of a single oral dose of ethanol 1.2 ml per kg body weight was analysed in 19 identical and 21 fraternal healthy, adult, un-selected male twin pairs. The heritability values of the rates of absorption, degradation and elimination of ethanol were 0.57, 0.41 and 0.46 respectively. Environmental factors, such as daily alcohol intake and smoking, increased the rate of elimination of blood alcohol. Intrasubject variation in ethanol metabolism was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
2

Year Published

1981
1981
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(42 citation statements)
references
References 16 publications
2
38
0
2
Order By: Relevance
“…The Widmark B60 (sometimes erroneously shortened to B) has been the classical parameter used to describe ethanol elimination rated and reported values (Kopun & Propping, 1977) are identical to the rate of 0.11 g h-' kg-' calculated in our study. Comparatively the more rational Michaelis-Menten rate, Vmax is remarkably similar at 0.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…The Widmark B60 (sometimes erroneously shortened to B) has been the classical parameter used to describe ethanol elimination rated and reported values (Kopun & Propping, 1977) are identical to the rate of 0.11 g h-' kg-' calculated in our study. Comparatively the more rational Michaelis-Menten rate, Vmax is remarkably similar at 0.…”
Section: Resultssupporting
confidence: 83%
“…This view has been perpetuated by many investigators with the use of arithmetic linear regression techniques and Widmark's coefficients (Kopun & Propping, 1977;Newman, Lehman & Cutting, 1937;Vesell, Page & Passananti, 1971). Haggard & Greenberg (1934) first suggested concentrationdependent elimination rates for ethanol and Lundquist & Wolthers (1958) showed that the Michaelis constant derived from experiments in man closely approximated that for alcohol dehydrogenase (ADH) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, smokers have faster alcohol metabolism than nonsmokers (Kopun and Propping, 1977;Morabia et al, 1999), and smoking increases alcohol consumption (Barrett et al, 2006). In rats, nicotine increases ethanol consumption and can result in reinstatement of alcohol-seeking behavior (Le et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Ethanol metabolism and elimination have been reported to range from 58 to 148 mg/kg/hr (Kopun and Propping, 1977), or 4 to 11 g/hr in a 70 kg man, with more rapid metabolism and elimination of ethanol noted in heavy drinkers (Jones, 1993) and chronic alcoholics (Nuutinen et al, 1985). Thus, the quantity of alcohol present in three standard drinks (one standard drink is considered equivalent to 13.6 g absolute ethanol; Sobell and Sobel, 1992) can be metabolized in 4 to 6 hr in an average male drinker.…”
Section: Discussionmentioning
confidence: 99%